Aplikasi Pembayaran Daring Berbasis Web di PT Goyong Bisnis Indonesia - Putri Lailatul Nikmah; Yunita Kristiyono; Johni S Pasaribu (STMIK IKMI Cirebon, 2021)
Abstract-. The use of information technology, computers and internet technology has penetrated in all areas of life, including the business world, including the processing of financial transactions such as online payments. Loan payments still often experience problems, they are still manual and less efficient for customers, especially when the customer is out of town. With the technological advances mentioned above, various innovations have been made to facilitate business interactions, including financial technology (fintech), which means financial technology, which is a technological innovation (breakthrough) carried out in the financial sector so that financial services can be carried out quickly, efficiently, and efficiently. and have a positive impact. This payment application contains company information, company terms and policies regarding lending, view the time and amount of online loans agreed between the customer and the company, make payments and view proof of payment and make investments and withdrawals of money. The design of this software is done with the freeware phpMyAdmin which supports MySQL database. This system development methodology is the classic waterfall method with object-oriented design using UML. This application has been used and helps the finance department in recording online loan payments and the customer can see proof of the transfer of the payment.